L'offre d'école Éléments pour une étude comparée des politiques éducatives au xixe siècle - Frijhoff, Willem (Homme et société, 1983)
In the 19th century, industrialisation and the systematic elaboration of educational policies were two concomitant phenomena; however, only the former is analysed usually in its international dimensions. For educational policies have until now been scarcely considered except front within a strictly national context, aiming to produce stereotypes and perpetuate myths firmly embedded in the collective consciousness of each individual country. In fact, these policies have assumed a supra-national character which urgently calls for a comparative approach. Only a just appreciation of the different factors - national and supra-national - and of the motivations both inside and outside the educational sector, will allow us to understand the conditions of their evolution and their chances of survival in the future. The selection of papers that are to be found in this book - papers presented at the Sevres International Conference on the occasion of the centinary of the French educational laws - wishes to help in the unravelling of this entanglement of factors, making the reader aware of what, in his intellectual and moral education, binds him to his own nation and what it is that makes him the citizen of a wider educational community.